EVALUASI USABILITY PORTAL AKADEMIK MAHASISWA MENGGUNAKAN METODE THINK ALOUD (STUDI KASUS: POLITEKNIK KEUANGAN NEGARA STAN) - Azzahra Cantika Maharani; Retno Indah Rokhmawati; Yusi Tyroni Mursityo (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
PKN STAN is an official higher education under the Financial Education and Training Agency (BPPK), Ministry of Finance of the Republic of Indonesia, which organizes Diploma Study Program education in the field of state finance. To support academic activities, the academic portal is used as the main tool. However, there are various problems on the student academic portal that disrupt academic activities. From these problems a usability evaluation is carried out using the think aloud method to find out the problem. From the problems found, recommendations for improving the user interface are given which will be re-evaluated to find out the comparison of the evaluation results. This study produced qualitative data, namely user feedback and quantitative data, in the form of assessments of three aspects of usability, namely effectiveness, efficiency, and satisfaction. The results of the qualitative comparison evaluation showed that the improvements made received more positive responses but there were still negative responses such as the need for adjustments to the improvements and components used. For quantitative results, the effectiveness level increased by 9.5%, the efficiency level increased by 2%, and the average value of user satisfaction increased by 21.4.